Effects of perceived leader emotional labour, ethical leadership and leader-member exchange on organizational commitment among the hotel operational staff - Kashani, Parisa Ehsan (2021)
Employee’s organizational commitment in service-oriented organizations including hotels is highly crucial and significant to meet customer satisfaction. Therefore, hotel operators are suggested to establish a good relationship between employers and employees. Past researchers suggested that organizational commitment could be affected by the leadership. Despite numerous studies conducted to test leadership style and organization commitment, limited studies have specifically addressed the impact of perceived leader emotional labour, ethical leadership, and leader-member exchange on organizational commitment in the hotel industry. Therefore, this research aims to investigate the influence of perceived ethical leadership, perceived leader-member exchange, and perceived leader emotional labour on organizational commitment among the operational staff within the hotel industry in Malaysia, particularly in 4-star and 5-star hotels. This study focused on operational staff’s perception of leaders, following the empirical evidence that employees could become less or not committed when weaknesses are identified on the leader ethical behaviour, leader-member exchange, and leader emotional labour. This situation could also affect the employees’ behaviours towards the customer, leading to negative customers’ perceptions and satisfaction. Due to the complex nature of this research model, the Partial Least Square-Structural Equation Modeling (PLS-SEM) is the most appropriate software for analysis of the research data due to its matching robustness. In this study, data were obtained from 422 hotel operational staffs who worked in the 4-star and 5-star hotels in Klang Valley. The beta coefficient, coefficient of determination, and predictive relevance of the constructs were analyzed for organizational commitment, followed by the results that indicated statistical significance. Following that, the effect sizes of the driver constructs (f2 and q2) were tested with small and medium-sized effects. All the hypothesized relationships were examined and supported at a 95% confidence interval with the corresponding t-values above the 1.96 threshold value. However, the relationship between the leader variety of emotional labour and organizational commitment failed to achieve significant value. Subsequently, perceived leader emotional labour was identified as intensity, frequency, deep acting, and surface acting that significantly influenced employee commitment. The model further tested the mediation role of perceived leader-member exchange on the relationship between perceived ethical leadership and organizational commitment. Results supported that there is partial mediation effect of perceived leader-member exchange on the relationship between perceived ethical leadership and organizational commitment. In summary, the results of the analysis have proven that perceived ethical leadership, perceived leader-member exchange, and perceived leader emotional labour significantly and positively influence organizational commitment in 4-star and 5-star hotels in Malaysia. The proposed model of this thesis could provide useful insights, which are especially pertinent to an improved understanding of emotional labour in the context of leadership and the outcomes of perceived leader emotional labour. However, these aspects were not adequately discussed in the current literature. The results indicated that the dimensions of perceived leader emotional labour, including deep acting, surface acting, frequency, and intensity influenced organizational commitment.